Predicting size at first sexual maturity from length/weight relationship: a case study with an Amazonian catfish - FREITAS, Tiago Magalhães da Silva (Universidade Federal do Pará, 2017)
Relationship between length and weight (LWR) is used to describe aspects concerning the life cycle of fish, but does not considers possible changes during the lifetime mainly due to the sexual maturation. Thus, this study aims to identify the size at first maturity of Auchenipterichthys longimanus (Siluriformes: Auchenipteridae) and infer if the reproductive engagement could change growth pattern, concerning the LWR. Estimates of the size at first maturity (L 50 ) were made by visual identification of gonadal development and through the gonadosomatic index (G SI ). L 50 was estimated as 12.5 cm for males and 13.0 cm for females when applied visual identification of gonads development. L 50 estimates increased to 13.05 cm for males and 13.7 cm for females when estimated from G SI values. LWR was adjusted by using a regular power function and through the polyphasic growth model, with proportionality and allometric coefficients changing in a two phases. The results indicate differences in the growth pattern concerning males and females, as well as polyphasic growth. The change in the growth pattern of the polyphasic LWR was estimated at 11.42 cm for males and 12.53 cm for females, suggesting that changes in the growth pattern can sign-out the attainment maturity in this catfish.